Microliter operation for determination of nitrate-nitrogen via simple zinc reduction and color formation in a well plate with a smartphone - Pheeraya Jaikang (2019)
© 2019 The Japan Society for Analytical Chemistry. We propose a simple greener colorimetric method for the determination of nitrate-nitrogen by operating on a 96-well microplate and using a smartphone camera as a simple detector. A slurry containing 0.3 mg zinc was used for reduction of nitrate to nitrite, the reduction solution was transferred to a 96-well microplate to react with Griess reagent to form a pink azo dye product. The color product image was captured and processed by a smartphone camera and ImageJ software, respectively. The limit of detection and limit of quantitation were 0.04 and 0.10 mg/L nitrate-nitrogen, respectively, for the smartphone camera. Application to real samples was demonstrated. The proposed method results showed no significant difference (at 95% confidence) with the hydrazine reduction method. The proposed method could be used as an alternative method for on-site analysis due to the advantages of portability and rapidity; duplicate run of 20 samples could be carried out simultaneously in 12 min.